Cord Care Practices: A Perspective of Contemporary African Setting - Afolaranmi, Tolulope O.; Hassan, Zuwaira I.; Akinyemi, Ofakunrin O.; Sule, Sarah S.; Malete, Matthew U.; Choji, Choji Pam; Bello, Danjuma A. (Frontiers in Public Health, 2018)
Background: Cord care is the series of steps applied in handling of the umbilical cord after delivery of the new born. Globally, an estimated 4 million deaths occur annually within the first 4 weeks of life and 1.5 million of these deaths is attributable to infections. In Nigeria, studies have reported umbilical cord infections accounting for between 10% and 19 % of neonatal admissions and resultant estimated 30 to 49% neonatal deaths. Hence, this study was conducted to assess the knowledge and practice of cord care within a contemporary setting. Methodology: This was a cross sectional study conducted among 324 mothers of children less than 59 months using a multi-stage sampling technique and SSPS version 20 was used for data analysis. Crude and adjusted odds ratios as well as 95% confidence interval were used in this study with a p-value of ≤ 0.05 considered statistically significant. Results: The mean age of the mothers in the study was 27.5± 6 years with majority of them having good overall knowledge and practice of cord care. Factors such residence in rural community (AOR = 0.26; 95% Cl = 0.0915 – 0.7230) and heath facility delivery (AOR = 7.0; 95% Cl = 4.7877 – 9.3948) were predictors of cord care practices. Conclusion: This study has brought to light the level of cord care practices with health facility delivery, place of residence and knowledge of cord care as its determinants.